PENINGKATAN KESADARAN KESEHATAN MENTAL KELUARGA MELALUI PROGRAM PSIKOEDUKASI DI BALAI KB KECAMATAN SAKO KOTA PALEMBANG - Zahra Salsabila Khoirunnisa; Firyal Kamilah; Nurisa Ramadhanti; Muhammad Sandy Davarel; Henny Yusalia (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Family mental health is an important aspect of individual and social well-being. However, public understanding of mental health remains relatively low and continues to be a common issue in society. This study aimed to examine the effectiveness of a family-based mental health psychoeducation program in improving public awareness and understanding of family mental health. The research employed a qualitative method with a case study approach at the Family Planning Center in Sako District, Palembang City. Data were collected through observation, interviews, and direct practice during the community service program. The activities included community socialization, the Emotion Bank program, counseling corners, maternal mental health psychoeducation, adolescent mental health education, and digitalization of community services. The findings showed that the program increased community participation, emotional openness, understanding of family mental health, and awareness of psychological well-being. Participatory and communicative approaches also helped participants feel more comfortable receiving education and psychological support effectively.